PENGARUH LOCUS OF CONTROL, PENGALAMAN KERJA DAN SISTEM REWARD TERHADAP PERILAKU ETIS AUDITOR - Raharjo, Evie Mutiara Tandyo (Jurnal Akuntansi Bisnis, 2013)
This research purposed to analyze the effect of locus of control, job experience and reward system toward auditor ethical behavior. Sample are the auditor in the KAP Semarang. Sampling technique used are purposive sampling method. Data from the distribution of questionnaires processed using SPSS to obtain the equation in the form of multiple regression. These results indicate that the locus of control and reward system affect auditor ethical behavior, meanwhile job experience did not affect auditor ethical behavior.